Rock climbing. - Kidd, Timothy W., ....-; Hazelrigs, Jennifer, ....- (Champaign : Human Kinetics, 2009)
Rock climbing has been growing in popularity since the 1930s, and it's no wonder. This exciting activity lets you spend time in the outdoors while challenging yourself both physically and mentally and bonding with friends and family. With the increasing availability of a variety of climbing venues, including indoor climbing gyms, it's easier than ever to try rock climbing. Rock Climbing is the perfect book for anyone who wants to develop the skills. Rock Climbing will help you explore one of the world's fastest-growing activities safely and successfully. The experts at the Wilderness Education Association ensure you learn proper technique, which is essential to a safe and enjoyable experience. They prepare you for your adventure with information on fitness and conditioning, equipment and gear selection, and nutrition. Safety skills are integrated throughout the book. You'll learn how you can use indoor climbing to practice basic skills before moving on to refine and build on those skills
In the outdoors. You'll find easy-to-follow instruction of climbing fundamentals, including knots, belaying, building anchor systems, moving on rock, descending, and lead climbing, giving you all the skills and knowledge you need to be a capable beginning climber. Throughout the book the authors share consumer, technique, and safety tips collected from their years of experience as both climbers and instructors. They also list Web sites to help you find climbing organizations, shop for equipment and gear, plan outdoor climbing trips, and more. The book also includes Success Check questions for each chapter that will help you test your climbing knowledge. Use Rock Climbing to join the millions of other climbing enthusiasts around the world. This complete resource will teach you all the essential information for a successful rock climbing adventure! Rock Climbing is part of the Outdoor Adventures series. This practical series provides you with the essential information so you can get ready and
Go. The Outdoor Adventures series prepares you with instruction in the basic techniques and skills so you can be on your way to an adventure in no time
Inhoudsopgave : Part I: Preparing for a Rock Climbing Adventure Chapter 1: Going Rock Climbing Chapter 2: Climbing Into Fitness Chapter 3: Indoor Climbing Chapter 4: Know Before You Go Chapter 5: Gearing Up for Rock Climbing Part II: On the Rock Chapter 6: Knots for Climbing Chapter 7: Managing Friction: The Skill of Belaying Chapter 8: Building Climbing Anchor Systems Chapter 9: Strength and Grace: Techniques for Movement on Rock Chapter 10: Descending Chapter 11: Lead Rock Climbing
Keywords: Rotsklimmen